Two new species of the previously monospecific genus Guipuzcosoma Vicente & Mauriès, 1980 from Spain, with establishment of Guipuzcosomatidae fam. nov. (Diplopoda: Chordeumatida) - Antić, Dragan; Mauriès, Jean-Paul (Zootaxa, 2022)
The present paper refers to the description of two new species of the previously monospecific genus Guipuzcosoma, viz., Guipuzcosoma karinae sp. nov. and G. reipi sp. nov. Given the unique combination of characters of this genus, we have established a higher taxonomic category, Guipuzcosomatidae fam. nov., which is clearly different from the family Vandeleumatidae, to which Guipuzcosoma was assigned earlier. Based on the structures of the anterior and posterior gonopods, we speculate that the new family may belong to the superfamilies Anthroleucosomatoidea or Cleidogonoidea. A diagnosis of the family, a brief description of the genus, as well as a diagnosis of all three species and detailed descriptions with illustrations of the two new species are presented. All three species were mapped. Additionally, some problems related to the taxonomy and classification within Chordeumatida, as well as the hypothetical association of the new family with some other chordeumatidans, are briefly discussed. Finally, the monospecific genus Miniusoma Mauriès, 2014 is transferred here from the family Vandeleumatidae to the family Anthogonidae.